Rekomendasi Penyekat RAAS Di Tengah - Tengah Pandemi Coronavirus - Joshua Henrina; Iwan Cahyo Santosa Putra; Hoo Felicia Hadi Gunawan; Irvan Cahyadi; Leonardo Paskah Suciadi (Jurnal Kardiologi Indonesia, 2020)
With a rapidly growing pandemic of coronavirus disease of 2019 (COVID-19), a public health emergency of international concern, the medical communities and national health systems are being tested for their preparedness. The culprit that is responsible for this viral respiratory disease, is a novel type of coronavirus, now identified as severe acute respiratory syndrome coronavirus - 2 (SARS-CoV2). At the present time, there are gaps in the knowledge regarding the safety of angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) for COVID-19 patients due to concern of ACE2, which is critical for viral entry and their levels are upregulated when using these (Renin Angiotensin Aldosterone System) RAAS blockers. ACE2 is a glycoprotein metalloprotease that plays an essential role in physiologic and pathological states and it is ubiquitously found in human organs. Despite sharing homology, ACE is different from ACE2, and while the former cleaves angiotensin 1 to angiotensin 2, the latter cleaves angiotensin two to angiotensin 1-7. Extrapolated from experimental animal studies, ACE2 and angiotensin 1-7 are important and protective for the lung physiology based on mice model of acute lung injury by various causes. Other evidence also demonstrates harm over benefits when stopping RAAS blockers, particularly in patients with cardiovascular disease, in which using these drugs are proven to be life-saving. In the light of the paucity of evidence derived from well-designed study, societies and colleges recommend continuing RAAS blockers until new evidence says otherwise.